A survey of national sustainable development indicators. (22nd January 2011) - Tasaki, Tomohiro; Kameyama, Yasuko; Hashimoto, Seiji; Moriguchi, Yuichi; , Hideo Harasawa
We surveyed sustainable development indicators (SDIs) adopted by 28 national governments, regions, and international organisations and compiled them into a database. The aims of this study were to understand the elements of sustainable development (SD), examine SDIs developed in certain fields and countries, and determine future tasks to improve SDI development. A total of 1, 790 indicators were surveyed and classified into 77 subcategories in four categories. Most of the indicators measured various SD elements, and the indicators reflected each country's developmental stage and specific concerns. Several advanced or unique indicators were also identified. Five major tasks in the future development of SDIs were identified: 1) creating time-conscious indicators; 2) measuring interactions between elements of a system; 3) dealing with transboundary issues in a national SDI system; 4) measuring SD quality (including subjective elements); 5) including ordinary citizens by showing the relationships between SDI and everyday life.